A Conceptual Framework of Raw Food Diet and Living Foods in Consumption Culture - Tolga Fahri Çakmak; Figen Sevinç (Journal of Tourismology)
The changes that come along with globalization in life styles are now evident in the tourism industry as well, and a variety of different diets have become available in the services provided by the industry. Further, eating and drinking habits, which differ according to the cultural features of their geography, are rapidly integrated into the existing consumptiondriven concept. In this sense, this study discusses the raw food diet, which has been popular around the world, within a conceptual framework, provides an insight into different practices regarding live foods as well as the perception of the raw food diet in consumption culture.